Inside out: Embodying prison boundaries - Cunha, Manuela Ivone P. da (2020)
This article compares materials drawn from fieldwork in a Portuguese women's prison in different decades, before and after the rise of concentrated incarceration that tightly interlocked this institution and a handful of heavily penalized urban neighbourhoods. As these worlds behind and beyond bars became socially and morally continuous, former intra-prison boundaries collapsed, entailing changes that included corporeal and sensorial aspects of prison experience. Taken as a window onto these changes, the imprisoned body is therefore described not as a bounded object of disciplinary power or as a site of resistance but as constituted first and foremost by social and moral relations, in a way that renders bodily experiences of confinement highly contextual. A comparison between forms more and less shaped by a particular prison–urban relation suggests that these experiences vary according not only to prison-specific circumstances, but also to social-specific circumstances.